(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:The leukocyte integrin that plays a major role in neutrophil activities is CD11b. In addition to mediating neutrophil adherence to endothelial cells, CD11b binds to the complement component iC3b and directs phagocytosis and intracellular lysis of microorganisms. Objective:To determine whether neutrophil activation, through the increased surface expression of the cell surface markers CD11a, CD11b, CD11c have a correlation with the values of complement components C3 and C4 in pregnant women with pre-eclampsia. Methods: This study was conducted at the AlKadhemiya Teaching Hospital. Patients were 60 pregnant women in labour subdivided into three groups: Group A: 20 pregnant women with severe pre-eclampsia. Group B: 20 pregnant women with mild-moderate pre-eclampsia. Group C: 20 normotensive pregnant women (control group). We performed the following laboratory measurements for all groups: total white blood cell WBC count, cell surface expression of CD11a, CD11b, CD11c by direct immunofluorescent technique, and serum complement C3 and C4 levels by radioimmunodiffusion method (RID). Results:There was a significant difference in neutrophil activation as detected by the cell surface expression of CD11a, CD11b, CD11c being higher in the pre-eclamptic group than the control group. The incidence of neutrophil activation was significantly higher among patients in group A compared to the other groups. There was a significant difference in the serum level of C3 and C4 in the pre-eclamptic group being higher in group A and B than group C. Conclusions:No correlation was found between the markers of neutrophil activation (CD11a, CD11b, CD11c) and the serum levels of (C3, C4) in the pre-eclamptic group. The incidence of adverse maternal and neonatal outcome is significantly higher among patients in group A compared to the other two groups. Key words: Preeclampsia, complement serum level, CD11a, CD11b, CD11C, neutrophil.